Ascorbic Acid in Charcot-Marie-Tooth Disease - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2009)
Ascorbic acid has been shown to reduce demyelination and improve muscle function in a transgenic mouse model of Charcot-Marie-Tooth disease (CMT1A).